A REGULATORY BASE OF CONTROLLING HEALTH CARE COMPETENCE OF TEACHING STAFF - Пятишева, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with a social-philosophical analysis of the regulatory base of Ukraine in relation to controlling health care competence of teaching staff.